2022
DOI: 10.3390/s23010276
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Learning-Based Collaborative Edge–Cloud Telemedicine System for Retinopathy of Prematurity

Abstract: Retinopathy of prematurity is an ophthalmic disease with a very high blindness rate. With its increasing incidence year by year, its timely diagnosis and treatment are of great significance. Due to the lack of timely and effective fundus screening for premature infants in remote areas, leading to an aggravation of the disease and even blindness, in this paper, a deep learning-based collaborative edge-cloud telemedicine system is proposed to mitigate this issue. In the proposed system, deep learning algorithms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…After entering the 21 st century, DL algorithms and AI technology have been consistently developed to promote their application in medicine [18] , and many studies have demonstrated that AI technology can aid in the screening, diagnosis, and treatment of diseases. At present, in the field of ophthalmology, AI technology has made remarkable achievements in the study of ocular surface diseases such as dry eye, pterygium, keratitis [19][20][21][22] , retinal vascular diseases such as DR, retinopathy of prematurity (ROP) [23][24][25][26][27][28] , age-related macular degeneration (AMD) [29][30][31] , and glaucoma [32][33][34] . However, few studies have investigated its application in the auxiliary diagnosis of RVO.…”
Section: Introductionmentioning
confidence: 99%
“…After entering the 21 st century, DL algorithms and AI technology have been consistently developed to promote their application in medicine [18] , and many studies have demonstrated that AI technology can aid in the screening, diagnosis, and treatment of diseases. At present, in the field of ophthalmology, AI technology has made remarkable achievements in the study of ocular surface diseases such as dry eye, pterygium, keratitis [19][20][21][22] , retinal vascular diseases such as DR, retinopathy of prematurity (ROP) [23][24][25][26][27][28] , age-related macular degeneration (AMD) [29][30][31] , and glaucoma [32][33][34] . However, few studies have investigated its application in the auxiliary diagnosis of RVO.…”
Section: Introductionmentioning
confidence: 99%
“…After entering the 21 st century, DL algorithms and AI technology have been consistently developed to promote their application in medicine [18] , and many studies have demonstrated that AI technology can aid in the screening, diagnosis, and treatment of diseases. At present, in the field of ophthalmology, AI technology has made remarkable achievements in the study of ocular surface diseases such as dry eye, pterygium, keratitis [19][20][21][22] , retinal vascular diseases such as DR, retinopathy of prematurity (ROP) [23][24][25][26][27][28] , age-related macular degeneration (AMD) [29][30][31] , and glaucoma [32][33][34] . However, few studies have investigated its application in the auxiliary diagnosis of RVO.…”
Section: Introductionmentioning
confidence: 99%
“…In reality we utilize technological tools of all kinds on a regular basis for multiple purposes (e.g., regulating household appliances and tracking energy consumption), which has contributed to the creation and transmission of tremendous amounts of personal data in seconds. In [4][5][6][7] future studies to expand the scope, range and maneuverability of healthcare technologies are addressed by the use of wireless networking technology.…”
Section: Introductionmentioning
confidence: 99%